Emerging Trends and Knowledge Structure in Indonesian Forest Management: A Bibliometric Analysis - Dewi Risnawati (Green Insight Solutions, 2026)
Indonesia’s tropical forests are central to global climate mitigation, biodiversity conservation, and the livelihoods of forest-dependent communities. However, forest management research in Indonesia remains fragmented and insufficiently synthesized, constraining its contribution to coherent scientific development and evidence-based policy. This study addresses this gap by systematically mapping research trends and knowledge structures in Indonesian forest management studies from 1986 to 2025. A total of 756 publications indexed in Scopus under the keywords “Forest Management” and “Indonesia” were analyzed using descriptive bibliometrics and science-mapping techniques, including co-authorship and co-citation analysis with VOSviewer. Research output increased markedly after 2015, with more than 80 articles published between 2021 and 2024. Keyword co-occurrence analysis identified five principal thematic clusters: ecological–silvicultural research; climate change and carbon dynamics; governance and community forestry; spatial and regional analysis; and geographically focused case studies. Overlay visualization reveals a temporal shift from early emphases on logging, timber production, and tropical forest ecology to mid-period attention on deforestation, carbon accounting, and Reducing Emissions from Deforestation and Forest Degradation (REDD), and more recently toward governance-oriented themes such as community forestry, participation, and policy implementation after 2018. The knowledge structure is influenced by a limited number of prominent authors and institutions, supported by strong international collaboration networks, and increasingly framed within sustainable and adaptive forest management, community-based approaches, and social–ecological systems perspectives. Despite thematic progress, significant gaps remain, including limited longitudinal policy impact evaluation, weak integration of socio-ecological and spatial analyses, underrepresentation of regions such as Papua, and insufficient development of operational forest management models. This study offers the first multidimensional synthesis of Indonesian forest management research and underscores the need for integrated, community-responsive strategies to strengthen future policy and practice.